Prototype development of smart parking system powered by solar photovoltaic - M.Z.M. Nasir; S. Salimin; B. Chan; S.A. Jumaat (Institute of Advanced Engineering and Science, 2020)
This paper proposed the prototype of smart car parking powered by photovoltaic. There is probability that cars will hit the wall or car out from the parking lot. The main objectives of this research are to determine the power rating and sizing of PV panel suitable for smart car parking system and design an ultrasonic parking sensor circuit to alert any obstacle while parking and development the prototype of smart car parking using PV. Smart car parking consists of distance sensors, LED, Arduino UNO potentiometer, resistors, and Node MCU. Where, Arduino UNO as a microcontroller was coding to receive the signal from the sensor and transmit signal to LED to display the car distance condition. To measure the distance between sensor positions to a car, HC-SR04 ultrasonic distance sensor is used. Whenever a car come near to the sensor within range specified, the red, yellow or green LED will light up and send the condition happening to the smartphone application. The application build-up can display the real situation and the PV system can supply enough electricity to the smart car parking.